Evaluation of intensified behaviour change communication strategies in an artemisinin resistance setting. (December 2016) - Canavati, Sara; Beyl, Celine; Ly, Po; Shafique, Muhammad; Boukheng, Thavrin; Rang, Chandary; Whittaker, Maxine; Roca-Feltrer, Arantxa; Sintasath, David
Abstract Background In Cambodia, behaviour change communication (BCC) represents an integral component of malaria efforts aimed at fighting artemisinin resistant parasites and achieving elimination. The multi-pronged BCC interventions include interpersonal communication through village health volunteers (VHVs) and village malaria workers (VMWs), broadcasting malaria prevention, diagnosis and treatment messages via TV, radio and mobile broadcasting units (MBUs), distributing information education and communication (IEC) materials and introducing mobile malaria workers (MMWs) in endemic villages. Methods This was a cross sectional household survey using a stratified multi-stage cluster sampling approach, conducted in December 2012. A stratified multi-stage cluster sampling approach was used; 30 villages were selected (15 in each stratum) and a total of 774 households were interviewed. This survey aimed to assess the potential added effect of 'intense' BCC interventions in three Western provinces. Conducted 2 years after start of these efforts, 'non-intense' BCC (niBBC) interventions (e.g., radio or TV) were compared to "intense" BCC (iBBC) implemented through a set of interpersonal communication strategies such as VMWs, VHVs, mobile broadcasting units and listener viewer clubs. Results In both groups, the knowledge of the mode of malaria transmission was high (96.9 vs 97.2 %; p = 0.83), as well as of fever as a symptom (91.5 vs 93.5 %; p = 0.38). Knowledge of local risk factors, such as staying in the forest (39.7 vs 30.7 %; p = 0.17) or the farm (7.1 vs 5.1 %; p = 0.40) was low in both groups. Few respondents in either group knew that they must get tested if they suspected malaria (0.3 vs 0.1; p = 0.69). However, iBBC increased the discussions about malaria in the family (51.7 vs 35.8 %; p = 0.002) and reported prompt access to treatment in case of fever (77.1 vs 59.4 %; p < 0.01). Conclusion The use of iBCC supported positive improvements in both attitudes and behaviours among the population with regard to malaria compared to mass media (niBCC) only. The significantly increase in people seeking treatment for fever in iBCC villages supports Objective Five of the Strategic Plan in the Cambodia Malaria Elimination Action Framework (2016–2020). Therefore, this study provides evidence for the planning and implementation of future BCC interventions to achieve the elimination of artemisinin resistantPlasmodium falciparum malaria.